The Relationship Between Students' Critical and Creative Thinking Skills in Nutrition Concepts Within the Framework of Education for Sustainable Development - Liana, Tantri; Sinaga, Parlindungan; Rusyati, Lilit; Airin, Ayu Lita Permata (Universitas Islam Negeri Raden Intan Lampung, 2024)
In the context of the Fourth Industrial Revolution, equipping students with critical and creative thinking skills within the framework of Education for Sustainable Development is essential but remains insufficiently explored, particularly in relation to nutrition concepts. This study evaluates the critical and creative thinking skills of eighth-grade students at a private junior high school and examines the relationship between these skills in the context of Education for Sustainable Development and nutrition. A total of 62 students participated in the study, which employed a correlational design to analyze data from a written test comprising fifteen multiple-choice questions on critical thinking and eight essay questions on creative thinking. To minimize guessing, the critical thinking test included well-designed distractors. Descriptive analysis was followed by the application of the Spearman test to determine the correlation between critical and creative thinking skills. The results indicated low performance in both areas, with average scores of 31.61 for critical thinking and 43.34 for creative thinking. Furthermore, no significant correlation was found between the two skills, as the significance value of 0.126 exceeded the threshold of 0.05. The findings suggest that systematic planning and continuous learning are necessary to enhance these skills and improve academic performance. The study emphasizes the need for structured educational strategies to develop critical and creative thinking concurrently, thereby informing curriculum development to support Education for Sustainable Development goals and prepare students to address future sustainability challenges.